The Influence of Job Performance and Employee Competence on Job Promotion - Abdul Rahman (P3M STIEM BONGAYA, 2021)
The Effect of Job Performance and Employee Competence on Job Promotion at the Regional Development Planning, Research and Development Agency (Bappelitbangda) Takalar Regency. The purpose of this study was to determine the effect of job performance and employee competence on job promotion at the Regional Development Planning, Research and Development Agency (Bappelitbangda) Takalar Regency. The population in this study were 37 permanent employees at the Regional Development Planning, Research and Development Agency (Bappelitbangda) Takalar Regency and 37 employees at the same time as a sample. The methods in collecting data in this study are questionnaires, observations, and interviews. Methods of data analysis using descriptive methods and inferential statistical methods, namely by using multiple linear regression statistical methods to measure the effect of work performance and competence of employees on job promotion at the Regional Development Planning, Research and Development Agency (Bappelitbangda) Takalar Regency. Based on the F test and t test the independent variables (Job Performance and Employee competence) jointly and partially have a positive and significant effect on the dependent variable (Job Promotion). Through testing the correlation coefficient (R), it was found that the level of correlation between Job Performance and Employee Competence on Job Promotion was a strong relationship, namely 68.2%, while the remaining 31.8% was influenced by other factors.